2022
DOI: 10.1136/tc-2022-057461
|View full text |Cite
|
Sign up to set email alerts
|

The role of IQOS risk perceptions on cigarette smoking behaviours: results from a prospective pilot study

Abstract: BackgroundIQOS is a heated tobacco product marketed as an alternative to combustible cigarette smoking. Little is known about cigarette smokers’ IQOS health risk perceptions and if these risk perceptions impact IQOS use and cigarette smoking behaviour.MethodsAdult, daily, non-treatment-seeking cigarette smokers (n=27), naïve to IQOS, were recruited from Philadelphia, Pennsylvania, USA. Participants were introduced to IQOS and then completed measures of risk perceptions. Participants were given an IQOS 2.4 hold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Recent publications, including a commentary in Nature [60] and a comprehensive review [59], have reported higher smoking cessation rates in individuals using nicotine electronic cigarettes compared to those using nicotine replacement therapy. These findings align with what has been previously reported in systematic reviews and randomized controlled and population studies [61][62][63][64][65]. However, the current data are still insufficient to support unanimous recommendations in this regard [66,67].…”
Section: Discussionsupporting
confidence: 90%
“…Recent publications, including a commentary in Nature [60] and a comprehensive review [59], have reported higher smoking cessation rates in individuals using nicotine electronic cigarettes compared to those using nicotine replacement therapy. These findings align with what has been previously reported in systematic reviews and randomized controlled and population studies [61][62][63][64][65]. However, the current data are still insufficient to support unanimous recommendations in this regard [66,67].…”
Section: Discussionsupporting
confidence: 90%
“…In our experiment, the study groups consisted of both traditional cigarette smokers and users of modern methods of nicotine delivery to the body: e-cigarettes and heated tobacco products. Due to numerous modifications and marketing campaigns, the above-mentioned “new” devices that supply nicotine to the body are gaining enormous popularity among young people, leading to “renormalisation” of the smoking habit ( DeAtley et al, 2022 ; Harlow et al, 2022 ; Jankowski et al, 2022 ). Their high popularity is influenced by the fact that there are many flavors of e-cigarette liquids/cigarette sticks for heat-not-burn products on the market (over 8,000) ( Xu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Electronic cigarettes and heat-not-burn products, considered by the public to be less harmful, were supposed to become an alternative to traditional cigarettes. Electronic cigarettes are mechanical devices that heat special solutions for inhalation, giving the user a sensation similar to ordinary smoking ( DeAtley et al, 2022 ; Harlow et al, 2022 ). The liquid of e-cigarettes mainly consists of odorless carriers (propylene glycol, glycerol), nicotine, and a wide range of flavorings ( Leventhal et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our experiment, the study groups consisted of both traditional cigarette smokers and users of modern methods of nicotine delivery to the body: e-cigarettes and heated tobacco products. Due to numerous modifications and marketing campaigns, the abovementioned "new" devices that supply nicotine to the body are gaining enormous popularity among young people, leading to "renormalisation" of the smoking habit (DeAtley et al, 2022;Harlow et al, 2022;Jankowski et al, 2022). Their high popularity is influenced by the fact that there are many flavors of e-cigarette liquids/cigarette sticks for heat-not-burn products on the market (over 8,000) (Xu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Electronic cigarettes and heat-not-burn products, considered by the public to be less harmful, were supposed to become an alternative to traditional cigarettes. Electronic cigarettes are mechanical devices that heat special solutions for inhalation, giving the user a sensation similar to ordinary smoking (DeAtley et al, 2022;Harlow et al, 2022). The liquid of e-cigarettes mainly consists of odorless carriers (propylene glycol, glycerol), nicotine, and a wide range of flavorings (Leventhal et al, 2019).…”
Section: Introductionmentioning
confidence: 99%